Nanomaterials engineered for photothermal therapy in neural tumors and neurodegenerative diseases: biomaterial design, clinical mechanisms and applications - Zhu, Hanjing; Yang, Wei; Suo, Yijun; Liu, Ye; Zhan, Xinyi; Zhou, Jun; Chen, Zhiying; Wu, Xiangbing; Yin, Xiaoping; Bao, Bing (Frontiers in Bioengineering and Biotechnology, 2025)
The rising incidence of neural tumors and neurodegenerative diseases cause significant health, emotional, and financial burdens. Conventional treatments like surgery and chemotherapy often lack effectiveness. However, advancements in nanotechnology, particularly photothermal therapy (PTT), offer new hope. PTT is widely studied for neural tumors and neurodegenerative diseases due to its simplicity, rapid recovery, combined therapeutic potential, and compatibility with imaging techniques. This innovative approach could revolutionize the diagnosis and treatment of neural tumors and neurodegenerative diseases, addressing current limitations and improving outcomes. In this article, we offer a comprehensive overview of the rational design and engineering of various nanomaterials designed specifically for PTT applications in neural tumors and neurodegenerative diseases, including organic platforms such as liposomes, dopamine, etc. and inorganic platforms such as gold nanomaterials, carbon nanomaterials, etc. A comparative analysis of these platforms examines their biocompatibility and potential for biodegradation. It also assesses their manufacturing scalability, cost-effectiveness, regulatory challenges, and ultimate potential for clinical translation. We also update the therapeutic advances of PTT in neural tumors (Glioma, Peripheral nerve sheath tumors, Spinal metastases from in situ tumors and brain metastases) and neurodegenerative diseases (Alzheimer’s disease, Parkinson’s disease, Huntington’s disease), and systematically summarize the mechanisms of PTT application in neural tumors and neurodegenerative diseases. In the end, we provide an in-depth discussion of the advantages and disadvantages of PTT and the perspectives for its application in the above neurological disorders.